Architecture students conduct case study at Ipoh’s Stadium Indera Mulia / Mayamin Yuhaniz, Izzat Anuar and Amirul Amin Hj. Ismail - Yuhaniz, Mayamin; Anuar, Izzat; Hj. Ismail, Amirul Amin (Universiti Teknologi MARA, Perak, 2024)
Ipoh, May 16, 2024 – Final-year architecture students from the Programme of Architecture, College of Built Environment, Universiti Teknologi MARA, Perak Branch, Seri Iskandar Campus, visited Ipoh to study the renowned Stadium Indera Mulia at Kompleks Sukan Majlis Bandaraya Ipoh. The trip, organized by Ts. Izzat Anuar, aimed to provide students with a comprehensive understanding of the design and functionality of the indoor sports arena.